Profiles of technology-rich learning activities for early literacy and teachers’ roles in Korea - Boram No (Cogent Education)
This study aimed to identify the diversity as combinations of traditional and digital literacy activities in early childhood classrooms and also analyze the relationship between literacy activities and teachers’ literacy teaching competencies as well as classroom literacy environments. In a sample of 330 teachers of 3–5 year old children from kindergarten and childcare centers, latent profile analysis revealed four-profile groups: (1) low literacy activity classroom, (2) traditional literacy dominance classroom, (3) digital literacy dominance classroom, and (4) high literacy activity classroom. In addition, classroom literacy activity profile groups can be predicted by literacy teaching competencies in teachers and classroom literacy environments. These results highlight the influence of a high-quality literacy environment and teachers’ digital literacy teaching competencies on their classroom’s early literacy activity profiles. The study has implications for promoting literacy activities in early childhood classrooms.